2012
DOI: 10.1111/mec.12109
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the ability of Bayesian clustering methods to detect hybridization and introgression using an empirical red wolf data set

Abstract: Bayesian clustering methods have emerged as a popular tool for assessing hybridization using genetic markers. Simulation studies have shown these methods perform well under certain conditions; however, these methods have not been evaluated using empirical data sets with individuals of known ancestry. We evaluated the performance of two clustering programs, baps and structure, with genetic data from a reintroduced red wolf (Canis rufus) population in North Carolina, USA. Red wolves hybridize with coyotes (C. la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(82 citation statements)
references
References 50 publications
(70 reference statements)
5
77
0
Order By: Relevance
“…As observed by Bohling et al . [25], S tructure seems better than BAPS to describe an admixed individual, but it cannot assure that an individual is of pure lineage.…”
Section: Discussionmentioning
confidence: 99%
“…As observed by Bohling et al . [25], S tructure seems better than BAPS to describe an admixed individual, but it cannot assure that an individual is of pure lineage.…”
Section: Discussionmentioning
confidence: 99%
“…A3). The higher power of Structure to detect genetic pollution compared to BAPS has been previously noted by Bohling et al (2013). We took advantage of detailed background knowledge on the genetic make-up of the two parental species involved.…”
Section: Hybridization On the Veluwementioning
confidence: 99%
“…v.74, n.6, p.443-449, November/December 2017 hybridization occurs (Boecklen and Howard, 1997;Sanz et al, 2008;Hashimoto et al, 2014). Tests using different numbers of markers have demonstrated that the variation in these numbers is directly related to the differentiation between loci among parental species (Sanz et al, 2006;Bohling et al, 2013); that is, the greater the difference, the smaller the number of markers required in the analysis. This was confirmed in this study, where the markers were 100 % fixed between species and were useful for detecting even introgressive hybridization.…”
Section: Discussionmentioning
confidence: 99%